Clinical and functional outcomes of pre-contoured plate fixation in displaced intraarticular calcaneum fracture - Kumar Babu, B. L. S.; Bhavanasi, Bhaskar Amarnath; Reddy, Narreddy Jayasomeswar (International Journal of Research in Orthopaedics, 2020)
Background: We evaluated the clinical and functional outcome of intra-articular calcaneal fractures treated with pre-contoured plating. The functional outcome was measured by the American Orthopaedic Foot and Ankle Society (AOFAS) scoring system. Methods: Twenty-five adult patients with displaced intra-articular calcaneus fractures, treated with by open reduction and internal fixation using pre-contoured plates, and those who were available for follow up were evaluated for the outcomes such as operative procedure, anatomical reduction, postoperative hospital stays early mobilization and functional outcome postoperatively. Follow-up was at three, six and twelve months radiological and clinical union were also considered. Results: Twenty-five adult patients presented with calcaneal fractures were operated during the study period. The mean time for union of fracture was 12.5±1.8 weeks. When we assessed the functional outcome in those patients who had radiological and clinical union using AOFAS score, we found that 16 out of 23 (64%) had good results with mean AOFAS score of 83.5±2.0 and 7/25 (28%) had fair results with mean score of 73.3±1.3, and 2/25 (8%) had poor results with mean score of 54.0±8.5. In 2 out of 16 (12.5%) patients, with good AOFAS scores, implants were removed after one and a half year from the day of surgery after confirming complete union of the fracture. Conclusions: We believe that pre-contoured reconstruction plate fixation for displaced intraarticular calcaneus fracture is excellent in terms of the union of the fracture, attaining anatomical reduction. It gives better outcomes concerning the function and range of movements.